Understanding Loneliness in Older Adults: Reports from Experts by Experience to Reach Digital Solutions. Issue 7 (3rd October 2022) - Guerra, Sara; Sousa, Liliana; Carvalho, Rita; Melo, Sara; Ribeiro, Oscar
ABSTRACT: Loneliness is a subjective experience escalating worldwide and affecting older adults. Digital solutions can play a major role in addressing loneliness, although its use has been facing resistance due to scarce involvement of older adults in its design. MOAI LABS is an ongoing European project that adopts a co-design process to develop digital solutions to address loneliness in older adults. This study reports the experience of loneliness shared by a group of eight community-dwelling older Portuguese adults (aged 64 to 86 years old), who are "experts by experience" (who feel alone). Findings were obtained from two co-creation sessions that were audio-recorded, and transcribed. The data analysis was performed involving the research team and the "experts by experience." Three themes emerged: 1) loneliness as a detrimental "state of the soul"; 2) loneliness reinforced by features of the aging process; and 3) loneliness builds more loneliness. MOAI LABS co-design process of digital solutions will embrace these experiences and involve frontline gerontological social workers who have experience with older adults' loneliness.